Therapeutic efficacy of LysGH15 against necrotising pneumonia caused by Staphylococcus aureus in a rabbit model - Bowei Zhang; Liran Song; Yongran Wang; Meimei Zhang; Chong Chen; Hui Ning; Li Wang; Cao Qiu; Xinwu Wang; Changjiang Sun; Xin Feng; Wenyu Han; et al. (Frontiers in Veterinary Science)
IntroductionStaphylococcus aureus (S. aureus) is one of the most important zoonotic pathogens and can be transmitted to humans through the meat diet routes, causing necrotising pneumonia.MethodsThis study investigated the therapeutic effect of bacteriophage lysin LysGH15 on necrotising pneumonia in rabbit model caused by S. aureus.ResultsIn the in vitro experiments, 50 μg/mL LysGH15 not only significantly reduced the viable count (approximately 3.24 × 106 CFU/g) of chicken meat stored at 4°C for 48 h but also effectively reduced the viable count of chicken meat thawed at 4°C and 30°C, with reductions of approximately 1.42 × 106 CFU/g and 2.78 × 106 CFU/g, respectively. In the in vivo experiments, a single intranasal administration of 300 μg/rabbit increased the survival rate of rabbits to 60%. At 72 h postinfection, the number of bacteria in the lung tissues of the rabbits treated with LysGH15 was 7 × 104 CFU/g, which was significantly lower than that in the lung tissues of rabbits treated with PBS (7.76 × 106 CFU/g) or linezolid (6.38 × 105 CFU/g). In addition, LysGH15 treatment alleviated lung tissue damage in infected rabbits and significantly reduced the levels of Panton-Valentine leukocidin (PVL), alpha-toxin (Hla), and the cytokines IFN-γ, TNF-α, and IL-8 in their lung tissues, similar to those in rabbits treated with linezolid.DiscussionThese results suggest that LysGH15 has the potential to be used as a novel antimicrobial agent for the treatment of necrotising pneumonia caused by S. aureus.